Lactic Acid Fermentation by Lactobacillus leishmanii Exposed to Some Organic Compounds - Singh, S.P.; Shamim, Md.; K. Singh, Rabindra; K. Singh, Awadh; Nirala, M.K.; Kamal, K.P. (Asian Journal of Chemistry, 2012)
The influence of 3-chloro-4-hydroxy mendelic acid, ortho-nitrophenol, para-nitrophenol and chloro-theophylline on the fermentative production of lactic acid by Lactobacillus leishmanii has been studied and it has been found that all the compounds have been toxic at all the concentrations used for lactic acid production.